2015
DOI: 10.1016/j.engfracmech.2015.05.059
|View full text |Cite
|
Sign up to set email alerts
|

FEMME: A multi-scale Finite Element Microstructure MEshfree fracture model for quasi-brittle materials with complex microstructures

Abstract: Please cite this article as: Mora, L.S., James Marrow, T., FEMME: A multi-scale Finite Element Microstructure MEshfree fracture model for quasi-brittle materials with complex microstructures, Engineering Fracture Mechanics (2015), doi: http://dx. AbstractIn this paper we develop a very efficient Finite Element Microstructure MEshfree (FEMME) method to account for the effect of microstructure on quasi-brittle properties within finite element simulations of damage, improving the accuracy and computational cost o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 23 publications
0
24
0
Order By: Relevance
“…This method is described in detail in reference [22,35,36], and a brief summary is provided here only. The Meshfree framework has been developed to simulate fracture development, using the CA to calculate the damage in the microstructure.…”
Section: Three-dimensional Experimental Characterisation Of Microstrumentioning
confidence: 99%
See 3 more Smart Citations
“…This method is described in detail in reference [22,35,36], and a brief summary is provided here only. The Meshfree framework has been developed to simulate fracture development, using the CA to calculate the damage in the microstructure.…”
Section: Three-dimensional Experimental Characterisation Of Microstrumentioning
confidence: 99%
“…Once the displacements of the microstructural features are calculated with the MAM layer by solving equation 1, the displacements are mapped to the cells of the CA model. This is done with the exponential shape functions of the IPD or PD that interpolate the domain [22]. With the displacements of the cells, the strains are computed and evaluated against the critical strain of the material phase that it represents.…”
Section: Three-dimensional Experimental Characterisation Of Microstrumentioning
confidence: 99%
See 2 more Smart Citations
“…More recent methods include mesh-free approaches [15,16] where Barbieri et al [15] introduced new weight-functions for node enrichment and Nguyen et al [17] demonstrated the potential of phase field methods to simulate crack nucleation and propagation.…”
Section: Introductionmentioning
confidence: 99%